Myanmar’s agrifood system structure and drivers of transformation - Diao, Xinshen; Masias, Ian; Pauw, Karl; Thurlow, James; Boughton, Duncan; Ellis, Mia (International Food Policy Research Institute, 2023)
Myanmar initiated economic and political reforms in 2011, ushering in a period of rapid economic transformation. The country experienced strong annual average economic growth of close to 7 percent between 2011 and 2019. The rural economy and the agriculture sector were also transforming, characterized by accelerated rural out-migration from the sector, which was facilitated by favorable policy changes, increased trade, and improved road infrastructure (Filipski et. al. 2021). Rural wages rose (Belton et. al. 2021), and labor shortages, along with increased access to financing, led to a massive expansion of mechanization services (Win et al. 2018) and other rural nonfarm enterprises. However, the economic transformation was disrupted by the global COVID-19 pandemic in 2020 and the political crisis caused by the military coup d’état in 2021. During this recent period, Myanmar’s agrifood system was impacted by numerous shocks, including disruptions to the banking and local transportation systems, changes to international trade policies, rapidly depreciating currency, foreign exchange controls, increasing global commodity prices, and massive declines in income and access to credit, among others. In this brief, we focus on Myanmar’s agrifood system between 2011 and 2019 and evaluate the potential contributions of different value chains to driving agricultural transformation and welfare gains in the future.